ROLE OF ENCAPSULATED CALCIUM CARBIDE IN NITROGEN ECONOMY, GROWTH AND YIELD OF CROPS: A REVIEW - R. Mahmood; A. Ali; M. Yaseen; M. Ahmad (Journal of Animal and Plant Sciences, 2014)
Various types of nitrogen losses whither to the atmosphere or to lower soil layers, result in low fertilizer N-use efficiency of crop plants.Ammonia volatilization is the major source of N-loss particularly when fertilizers are broadcasted on surface of alkaline soils. Nitrogen loss as NH3 can be decreased by alternative methods to broadcast like placement and side dressing. However, incorporation increases the soil-fertilizer contact and results in an increase in nitrification.Excess amount of nitrate formed during nitrification losses through leaching or denitrification. The loss of incorporated fertilizer nitrogen can be reduced by nitrification inhibition.A number of commercially available compounds have been reported as nitrification inhibitors (NI,s) but their effectiveness is limited due to one or the other reasons. Acetylene is another NI and owing to gaseous nature its application and maintenance in soil is difficult. To solve this problem, a suggested approach is to encapsulate calcium carbide with some hydrophobic materialto slow down spontaneous reaction of CaC2 with water and produce acetylene in soil. Encapsulated calcium carbide (ECC) application to soil inhibits nitrification, reduces nitrate leaching, nitrous oxide emissions and improves nitrogen uptake in favor of nitrogen use efficiency of crop plants. Type of encapsulation, and time, rate and depth of application of ECC significantly affect the efficacy of the approach. Another aspect of ECC released acetylene is its biological reduction to ethylene,a gaseous plant hormone which also has remarkable effects on plant growth. In this article various aspects of ECC application in crop production are discussed and research gaps are pointed out.
Keywords: nitrification inhibition; encapsulated calcium carbide; acetylene; ethylene; nitrate leaching; denitrification